Acidity Control Utilizing Different Soil Management Methods in Italian Ryegrass and Silage Maize Production Systems - Nogaroli,Jéssica Alves (2020)
Abstract This study examined the effects of liming on soil acidity and base saturation (V) in Italian ryegrass (ryegrass) and silage maize production systems over the medium-term. A split-plot design with four replications was employed on Humic Hapludox. The plots consisted of four soil management methods: conventional tillage (CT), minimum tillage (MT), no-tillage (NT) and chiselled NT (CNT). Within the split plots, ryegrass was used as cover crop (CC), silage (S), and integrated crop-livestock (ICL) system. Following ryegrass phytomass the maize was sowed. Once the maize had been cut with a silage machine, soil samples were collected from the layers 0-5, 5-10, 10-15, 15-20 and 20-30 cm at 24 and 60 months after liming. The attributes pH, H+Al, exchangeable aluminium (Al3+), and V were evaluated. The highest pH and V values were observed in the 0-5 cm layer in NT. The CNT did not result in improvement of acidity conditions or V. The ryegrass as S and ICL decreased soil acidity from 10 cm layer. NT combined with ICL provided soil acidity improvements 60 months after liming. Therefore, the exploration of winter with Italian ryegrass may elicit greater benefits in deep soil layers than cover crops.